Inhibition of HMGB1/RAGE-mediated endocytosis by HMGB1 antagonist box A, anti-HMGB1 antibodies, and cholinergic agonists suppresses inflammation - Huan Yang; Hui Liu; Qiong Zeng; Gavin H. Imperato; Meghan E. Addorisio; Jianhua Li; Mingzhu He; Kai Fan Cheng; Yousef Al-Abed; Helena E. Harris; Sangeeta S. Chavan; Ulf Andersson; et al. (BMC, 2019)
Abstract Background Extracellular high mobility group box 1 protein  (HMGB1) serves a central role in inflammation as a transporter protein, which binds other immune-activating molecules that are endocytosed via the receptor for advanced glycation end-products (RAGE). These pro-inflammatory complexes are targeted to the endolysosomal compartment, where HMGB1 permeabilizes the lysosomes. This enables HMGB1-partner molecules to avoid degradation, to leak into the cytosol, and to reach cognate immune-activating sensors. Lipopolysaccharide (LPS) requires this pathway to generate pyroptosis by accessing its key cytosolic receptors, murine caspase 11, or the human caspases 4 and 5. This lytic, pro-inflammatory cell death plays a fundamental pathogenic role in gram-negative sepsis. The aim of the study was to identify molecules inhibiting HMGB1 or HMGB1/LPS cellular internalization. Methods Endocytosis was studied in cultured macrophages using Alexa Fluor-labeled HMGB1 or complexes of HMGB1 and Alexa Fluor-labeled LPS in the presence of an anti-HMGB1 monoclonal antibody (mAb), recombinant HMGB1 box A protein, acetylcholine, the nicotinic acetylcholine receptor subtype alpha 7 (α7 nAChR) agonist GTS-21, or a dynamin-specific inhibitor of endocytosis. Images were obtained by fluorescence microscopy and quantified by the ImageJ processing program (NIH). Data were analyzed using student's t test or one-way ANOVA followed by the least significant difference or Tukey's tests. Results Anti-HMGB1 mAb, recombinant HMGB1 antagonist box A protein, acetylcholine, GTS-21, and the dynamin-specific inhibitor of endocytosis inhibited internalization of HMGB1 or HMGB1-LPS complexes in cultured macrophages. These agents prevented macrophage activation in response to HMGB1 and/or HMGB1-LPS complexes. Conclusion These results demonstrate that therapies based on HMGB1 antagonists and the cholinergic anti-inflammatory pathway share a previously unrecognized molecular mechanism of substantial clinical relevance.